Diffusion-Weighted Magnetic Resonance Imaging in Maxillary Sinuses Inflammatory Diseases: Report of Three Cases and Literature Review - Luciana Munhoz; Reinaldo Abdala Júnior; Rogério Abdala; Junichi Asaumi; Emiko Saito Arita (Stilus Optimus, 2018)
Background: Magnetic resonance imaging is considered a preferable imaging examination in the diagnosis of inflammatory maxillary sinus disease and can provide precise sinonasal characterization. Diffusion-weighted magnetic resonance imaging and apparent diffusion coefficient are complementary magnetic resonance imaging tools that can be applied to the differentiation of sinus diseases. In this report, 3 cases of inflammatory maxillary sinus diseases imaging findings considering diffusion-weighted magnetic resonance imaging features were described. Additionally, a literature review considering the use of diffusion-weighted magnetic resonance imaging in inflammatory lesions is provided. Methods: The cases reported were: presence of air-fluid levels, mucosal thickening and a mucous retention cyst. Conventional magnetic resonance imaging and apparent diffusion coefficient (ADC) maps, with ADC values were demonstrated. In the literature review, the studies considering inflammatory lesions were detailed, as well as ADC values established by investigators. Results: ADC values for presence of air-fluid levels, mucosal thickening and mucous retention cyst were respectively: 1.99 x 10(-3) mm(2)/s; 1.83 x 10(-3) mm(2)/s; 2.05 x 10(-3) mm(2)/s. Conclusions: It was observed that apparent diffusion coefficient values from the inflammatory lesions described in this report were different and apparent diffusion coefficient may be useful in the differentiation of these maxillary sinus alterations. Further larger sample investigations considering apparent diffusion coefficient values focusing in inflammatory lesions are recommended. The lack of studies considering the use of diffusion-weighted magnetic resonance imaging on inflammatory diseases diagnostic was the major limitation to the literature review.